2005
DOI: 10.1038/sj.ejcn.1602299
|View full text |Cite
|
Sign up to set email alerts
|

Basal metabolic rate and thyroid hormones of late-middle-aged and older human subjects: the ZENITH study

Abstract: Objective: This paper describes baseline data on basal metabolic rate (BMR), thyroid hormone levels and body composition of middle-aged and older people participating in the ZENITH project and the correlation of thyroid hormone levels with zinc status. Design: A multicentre prospective intervention study employing a randomised double blind design. Setting: Clermont-Ferrand, Theix (France), Coleraine (Northern Ireland), Grenoble (France), Rome (Italy). Interventions: BMR has been measured on a subsample of 70 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The factors associated with BEE have mainly been investigated in non‐diabetic humans. Age, fat mass, fat‐free mass/muscle mass, sympathetic nerve activity and thyroid hormone are all associated with BEE. However, these relationships remain unclear in humans with diabetes, who are associated with an increased risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The factors associated with BEE have mainly been investigated in non‐diabetic humans. Age, fat mass, fat‐free mass/muscle mass, sympathetic nerve activity and thyroid hormone are all associated with BEE. However, these relationships remain unclear in humans with diabetes, who are associated with an increased risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Such an increase was not observed by Wada and King [22] . More recently, Meunier et al [33] reported a moderate negative correlation between total T 4 and red blood cell zinc (r = -0.12, p ! 0.02) in middleaged to older adults; however, they did not supplement their subjects with zinc.…”
Section: Thyroid Hormone Concentrationsmentioning
confidence: 99%
“…Although endocrine effects have to be separated from alterations of body composition and PA behavior with aging, RMR is lower in older individuals, potentially even after adjusting for differences in body composition [ 43 ]. The age-related decline of RMR, however, cannot fully be ascribed to alterations of body composition or differences in thyroid hormone status [ 55 ].…”
Section: Physiological Changes In Older Athletesmentioning
confidence: 99%